2014
DOI: 10.3109/00365548.2013.879994
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis C in Swedish subjects receiving opiate substitution therapy—Factors associated with advanced fibrosis

Abstract: Chronic hepatitis C in Swedish subjects receiving opiate substitution therapy-Factors associated with advanced fibrosis.OGIONWO JERKEMAN, ANNA; Westin, Johan; Lagging, Martin; Norkrans, Gunnar; Lidman, Christer; Frimand, Jan; Simonsberg, Christian; Kakko, Johan; Widell, Anders; Björkman, Per Link to publication Citation for published version (APA): Jerkeman, A., Westin, J., Lagging, M., Norkrans, G., Lidman, C., Frimand, J., ... Björkman, P. (2014). Chronic hepatitis C in Swedish subjects receiving opiate subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…In addition, they have a higher prevalence of factors that both increase overall morbidity and mortality (such as HIV and HBV co‐infection, tobacco and alcohol use); factors that also are associated with progression of HCV related liver fibrosis . We have recently reported a high prevalence of liver fibrosis in OST recipients with chronic hepatitis C . The findings from the current study suggest that if the excess mortality during active injection drug use can be reduced, chronic liver disease may emerge as an increasingly important health problem among PWID.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, they have a higher prevalence of factors that both increase overall morbidity and mortality (such as HIV and HBV co‐infection, tobacco and alcohol use); factors that also are associated with progression of HCV related liver fibrosis . We have recently reported a high prevalence of liver fibrosis in OST recipients with chronic hepatitis C . The findings from the current study suggest that if the excess mortality during active injection drug use can be reduced, chronic liver disease may emerge as an increasingly important health problem among PWID.…”
Section: Discussionmentioning
confidence: 66%
“…Treatment uptake of HCV in active PWID has historically been low in Sweden and treatment in the OAT population also limited. Previous data, before the DAA era, showed that the overall lifetime uptake of HCV treatment among PWID on OAT was between 1 and 6% [ 34 36 ]. However, an observational study with data from the Swedish Prescribed Drug Registers noted an estimated cumulative DAA treatment uptake of 28% among OAT participants between 2014 and 2017 [ 37 ].…”
Section: Introductionmentioning
confidence: 99%